Unveiling the YouTube addiction: Understanding the spectrum of digital dependency - Rajalakshmi Mahendran; Subramoniam Abiharini; Archana Subbaraj (Journal of Family Medicine and Primary Care)
Background: Excessive use of YouTube is increasingly being as a source of technological addiction in both adolescent and adult population worldwide. Objective: The aim of this study is to assess YouTube addiction among adolescents and adults and the ways to reduce its usage. Methods: After obtaining Institutional ethical clearance and informed consent, we collected data from adolescent and adult male and female using a 22-item YouTube addiction scale (YAS) questionnaire. Face-to-face interview was conducted by the principal investigator. The principal component analysis (PCA) of the YAS questionnaire was performed. Manual content analysis was conducted for the qualitative data. Results: We enrolled 54 (50.9%) male and 52 (49.1%) female participants. The majority of them use YouTube and Instagram. Severely addicted were 38.7%, who spent all seven days watching YouTube videos. A principal component analysis revealed a four-component YAS structure based on an eigenvalue cutoff (>1), Kaiser-Meyer-Olkin (KMO) measure of sampling adequacy was more than 0.5, and Bartlett’s test of sphericity was <0.001. We grouped 22 items into four dimensions: Impaired control, decrease alternate pleasure, intense desire, and measures taken to reduce usage. Conclusion: Behaviour modification needed to promote healthier YouTube usage habits.